2012
DOI: 10.1126/science.1218740
|View full text |Cite
|
Sign up to set email alerts
|

Eddy-Driven Stratification Initiates North Atlantic Spring Phytoplankton Blooms

Abstract: Springtime phytoplankton blooms photosynthetically fix carbon and export it from the surface ocean at globally important rates. These blooms are triggered by increased light exposure of the phytoplankton due to both seasonal light increase and the development of a near-surface vertical density gradient (stratification) that inhibits vertical mixing of the phytoplankton. Classically and in current climate models, that stratification is ascribed to a springtime warming of the sea surface. Here, using observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
439
4
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(465 citation statements)
references
References 39 publications
21
439
4
1
Order By: Relevance
“…This variability likely reflects both enduring climatological differences within regions and transient, localized processes, such as storms, mesoscale eddies, horizontal advection of distinct water masses, tidal mixing and bathymetry (Greene et al, 2012;Mahadevan et al, 2012;McGillicuddy et al, 2007). Finally, our analysis compares well to the seasonal averages described for the Gulf of Maine by Thomas et al (2003) and differ from the descriptions of bloom initiation in Ji et al (2007) and Song et al (2010) because their study domains extended further north and eastward over the shallower areas of the Scotian Shelf.…”
Section: Discussionsupporting
confidence: 56%
“…This variability likely reflects both enduring climatological differences within regions and transient, localized processes, such as storms, mesoscale eddies, horizontal advection of distinct water masses, tidal mixing and bathymetry (Greene et al, 2012;Mahadevan et al, 2012;McGillicuddy et al, 2007). Finally, our analysis compares well to the seasonal averages described for the Gulf of Maine by Thomas et al (2003) and differ from the descriptions of bloom initiation in Ji et al (2007) and Song et al (2010) because their study domains extended further north and eastward over the shallower areas of the Scotian Shelf.…”
Section: Discussionsupporting
confidence: 56%
“…4). This broad trend supports the hypothesis that calcite wt% is a measure of water stratification and temperature Mahadevan et al, 2012;Thórdardóttir, 1984). There is a statistically significant relationship (n = 26, p = 0.0002) between 50 m water temperature and the weight% of carbonate for all sites, but excluding Djupall, which for its temperature, has anomalously high carbonate values.…”
Section: The Oceanographic Climatic and Physical Backgroundsupporting
confidence: 66%
“…In both cases, the length of the series poses a great limitation to ascribe observed trends to climate change (Henson et al, 2010), although it revealed a clear signature of climate forcing on interannual changes in bloom statistics. Other problems include the difficulties to interpret changes in remotely sensed chl a concentration (see Materials and Methods), the indirect treatment of mixed layer dynamics and the lack of some important drivers of phytoplankton and bloom dynamics, like advection and sub-mesoscale features (Lehahn et al, 2007;Mahadevan et al, 2012). Another interesting aspect revealed by this study was the importance of taking into account potential differences between satellite missions and between chl a algorithms (see the Supporting Text in the Supporting Information).…”
Section: Changes In Phytoplankton Seasonalitymentioning
confidence: 97%